The Strategic Effects of Smoking Bans - Christian Bauer; Jörg Lingens (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2008)
We analyse the welfare effects of a publicly imposed smoking ban in privately owned places like bars. In an economy where households have heterogenous (positive and negative) attitudes towards smoking bans, bars can use the smoking regime choice as a strategic variable. In doing so, bars may endogenously implement a product differentiation. Focusing on the possibility to separate markets, we derive the Nash equilibrium of the decentral economy in a setting in which duopoly bars compete in capacity and choose the smoking regime. We show how the smoking regime choice is a function of the heterogeneity of households. Moreover, we show that the social planer implements the smoking regime obtained in the decentral economy. As such, imposing smoking bans is welfare decreasing in an economy in which bar landlords chose to allow smoking.
Keywords: L13; I18; D61; 330; Smoking Ban; Endogenous Product Differentiation